2014
DOI: 10.3390/v6020727
|View full text |Cite
|
Sign up to set email alerts
|

Identification by Mass Spectrometry and Immune Response Analysis of Guinea Pig Cytomegalovirus (GPCMV) Pentameric Complex Proteins GP129, 131 and 133

Abstract: Development of a vaccine against congenital infection with human cytomegalovirus (HCMV) is a major public health priority. A potential vaccine target receiving considerable recent attention is the pentameric complex (PC) of HCMV proteins consisting of gL, gH, UL128, UL130, and UL131, since some antibodies against these target proteins are capable of potently neutralizing virus at epithelial and endothelial cell surfaces. Recently, homologous proteins have been described for guinea pig cytomegalovirus (GPCMV), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Both N13R10 and ⌬145 have a 4-bp deletion that frameshifts the gp129 ORF (25) and renders these viruses unable to assemble a pentameric complex (PC) composed of gH, gL, gp129, gp131, and gp133 (42)(43)(44)52). In this respect, they resemble the HCMV Towne strain variants that comprise the Towne vaccine, which also contains a mutation that disrupts expression of a PC subunit (17).…”
Section: Discussionmentioning
confidence: 99%
“…Both N13R10 and ⌬145 have a 4-bp deletion that frameshifts the gp129 ORF (25) and renders these viruses unable to assemble a pentameric complex (PC) composed of gH, gL, gp129, gp131, and gp133 (42)(43)(44)52). In this respect, they resemble the HCMV Towne strain variants that comprise the Towne vaccine, which also contains a mutation that disrupts expression of a PC subunit (17).…”
Section: Discussionmentioning
confidence: 99%
“…Yamada et al [117] first described a region of the GPCMV genome which appeared to contain homologues of HCMV PC and, more recently, Auerbach et al [118] concluded that the guinea pig genes GP129, GP131 and GP 133 are the homologues of the HCMV genes UL128, UL130 and UL131, and that the relevant recombinant proteins are immunoreactive with convalescent sera from infected animals [119]. Thus, the protein products of GPCMV GP129, 131 and 133 locus were referred to as the GP PC, and the mutations acquired during passaging in fibroblasts attenuated virus pathogenicity [120], whereas repair resulted in congenital transmission, intrauterine growth restriction and elevated pup mortality.…”
Section: Development Of An Hcmv Vaccine: Potential Role Of the Pcmentioning
confidence: 99%
“…Western blot assays were conducted using standard protocols, with virus particles purified as described previously (15). Virus particles from N13R10, r129, and SG virus (passaged once in GPL cells; 10 g per lane) were separated by SDS-PAGE, transferred to nitrocellulose membranes, and probed using antibodies specific for GPCMV proteins ( Fig.…”
Section: Virus and Cells Cell Culture Propagation Of Virus Was Carrimentioning
confidence: 99%
“…GPCMV glycoprotein B (gB) was detected using murine monoclonal anti-gB antibodies IE3-21 (3) or 29.29. Rabbit and guinea pig antisera specific to GP129, GP131, and GP133 are described elsewhere (15). The guinea pig antiserum to GP129 was raised against a glutathione S-transferase (GST) fusion protein, including GP129 residues Asn 146 through Lys 179 of the GP129 ORF, and was therefore not predicted to react with any putative truncated forms of GP129 corresponding to the first 101 codons of the ORF that might be expressed in the context of the 4-bp deletion mutation.…”
Section: Virus and Cells Cell Culture Propagation Of Virus Was Carrimentioning
confidence: 99%
See 1 more Smart Citation